Industrial development review series : Thailand - United Nations Industrial Development Organization; UNIDO (United Nations Industrial Development Organisation (UNIDO), Vienna, 1985)
This is the review of the country survey and studies on developing countries prepared by the country studies branch.
oo 11/04/2019
Loans
Keywords: Industrial development; Thailand